The Utilization of Appropriate Procedure in the Administrative Court of First Instance of Thailand. - mongphol, Perathum (CMU Journal of Law and Social Sciences, 2024)
One component of the rule of law is the effective, fair, and prompt administration of justice. According to statistics on case filings in the lower courts of Thailand, from their inception until March 31, 2567, B.E. (2024), there were 149,706 cases filed, out of which 133,052 cases were concluded, leaving 16,654 cases pending. The duration of case adjudication depends on the workload of the presiding judges. For instance, if a judge has no more than 48 cases, it would take approximately 2 years and 6 months to adjudicate a case. If the caseload ranges from 49 to 72 cases, the adjudication time extends to about 3 years, 1 month, and 15 days, with an additional 0.25 times added to each stage for every 24 cases. Consequently, cases with minor claims or straightforward circumstances often fail to receive prompt adjudication proportional to the justice deserved. While expedited proceedings are employed to alleviate delays, they are only applicable when the court deems standard proceedings could cause severe and irreparable harm to the claimant or impede state administration or public services. Therefore, cases with minor claims or straightforward circumstances outside these conditions cannot undergo expedited proceedings. Allowing such cases to proceed through standard procedures may result in claimants not receiving timely redress. The analysis of the problem concerning the utilization of appropriate trial methods to address delays resulting from case adjudication in this lower court necessitates an examination of the administrative system within the judicial process of the lower court, measures to regulate trial proceedings, and the balance of power within the administrative organization of the lower court. This comparison should be made against the procedural laws governing trial methods in foreign jurisdictions’ lower courts or courts vested with authority over cases of similar nature, to understand how they have organized their judicial processes to expedite case adjudication. Additionally, it aims to encourage individuals with minor cases to utilize their rights in court more effectively. The research revealed that foreign administrative courts or courts vested with jurisdiction over administrative cases typically bifurcate the trial proceedings into categories: regular administrative cases and cases involving minor claims with straightforward circumstances. This bifurcation aims to ensure that such cases are adjudicated in a manner commensurate with the level of justice warranted. Consequently, the author advocates for a reform of the administrative trial process within the Administrative Court of First Instance, entailing a similar division between regular administrative cases and those involving minor claims with uncomplicated circumstances. Moreover, it is suggested that the trial format be customized to align with the nature of the claimant’s petition or the complexity of the case.